Simulink based Analysis and Realization of Line Commutated Grid Tied Inverter for Renewable Energy Applications - S. Badie Asghar; R. K. Singh (Journal of Electronic Design Engineering, 2016)
Non-conventional energy resources are increasingly used to fulfill load demands. Before using such energy sources the very important thing is analysis at the basic level. This paper presents analysis and realization of line commutated grid tied inverter for renewable energy applications. The current-voltage and power-voltage characteristics of solar PV array changes as parameters like solar insolation and temperature changes. These characteristics are found and realized using MATLAB software. Line commutated inverters are discussed in this paper for grid interactive modes of operations.